A multicenter cohort study on mapping of lymph node metastasis for splenic flexural colon cancer. Issue 2 (18th September 2022) - Watanabe, Jun; Kanemitsu, Yukihide; Suwa, Hirokazu; Kakeji, Yoshihiro; Ishihara, Soichiro; Shinto, Eiji; Ozawa, Heita; Suto, Takeshi; Kawamura, Junichiro; Fujita, Fumihiko; Itabashi, Michio; Ohue, Masayuki; et al.
Abstract: Aim: There have been no reports of searching for metastases to lymph nodes along the accessory middle colic artery (aMCA). The aim of this study was to investigate the metastasis rate of the aMCA for splenic flexural colon cancer. Methods: Patients with histologically proven colon carcinoma located in the splenic flexure, clinically diagnosed as stage I‐III were eligible for this study. Patients were retrospectively and prospectively enrolled. The primary endpoint was frequency of lymph node metastasis to the aMCA (station 222‐acc and 223‐acc). The secondary endpoint was the frequency of lymph node metastasis to the middle colic artery (MCA) (station 222‐lt and 223) and left colic artery (LCA) (station 232 and 253). Results: Between January 2013 and February 2021, a total of 153 consecutive patients were enrolled. The location of the tumor was 58% in the transverse colon and 42% in the descending colon. Lymph node metastases were observed in 49 cases (32%). The presence of aMCA rate was 41.8% (64 cases). The metastasis rates of stations 221, 222‐lt, and 223 were 20.0%, 1.6%, and 0%, and stations 231, 232, and 253 were 21.4%, 1.0%, and 0%, respectively. The metastasis rates of stations 222‐acc and 223‐acc were 6.3% (95% confidence interval: 1.7%‐15.2%) and 3.7% (95% confidence interval: 0.1%‐19%), respectively. Conclusions: This study identified the distribution of lymph node metastases from splenic flexural colon cancer. If the aMCA is present, this vessel should be targeted for dissection, taking into account the frequency of lymph node metastasis. Abstract : How often lymph node metastases occur in the lymph nodes along the accessory middle colic artery (aMCA) is unclear. This study showed that the metastasis rates of the intermediate lymph node (stations 222‐acc) and main lymph node (stations 223‐acc) of the aMCA were 6.3% and 3.7%, respectively, with the presence of aMCA (41.8%). If the aMCA is present, this vessel should be targeted for dissection, taking into account the frequency of lymph node metastasis.